"You Dinked My Battleship": The Dinking Game for Pickleball Skill Learning. (4th July 2019) - Zagrodnik, James
Abstract : Pickleball is being played and taught all over the world. Requiring a combination of touch and power shots, pickleball is a game of both patience and opportunistic play. Despite its popularity, limited teaching resources currently exist for physical educators on how to teach critical pickleball skills in their classroom. "You Dinked My Battleship" is a skill-specific game invented for learners to practice and enhance their skills in the most important shot of the pickleball game — the dink — in a fun and potentially competitive atmosphere. With seven different progressive challenges, this fast-paced game provides a high rate of active learning time and opportunities to learn for all types of students. Easy to set up with minimal equipment and simple rules, the game can be played with maximum participation no matter the class size. Effectively teaching pickleball skills in physical education could lead to lifelong participation in pickleball and possible skill transfer for more complex racquet sports.